2020
DOI: 10.1186/s12871-020-01125-4
|View full text |Cite
|
Sign up to set email alerts
|

Pain management after ambulatory surgery: a prospective, multicenter, randomized, double-blinded parallel controlled trial comparing nalbuphine and tramadol

Abstract: Background: Postoperative pain in ambulatory surgery is a multifactorial issue affecting patient satisfaction, time of discharge, and rehospitalization. This study evaluated the efficacy and safety of nalbuphine for the treatment of postoperative pain after ambulatory surgery, relative to tramadol. Methods: This multi-center, randomized, double blind, and controlled study was conducted at 10 centers. In accordance with the inclusion criteria, 492 ambulatory surgery patients were recruited. These patients had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Moreover, because nalbuphine has very weak reactivity with delta (δ) receptors, this drug is expected to cause reduced irritability or anxiety 5,6 . In the clinical setting, pretreatment with nalbuphine can effectively reduce propofol‐induced injection pain and propofol consumption as well as ameliorate postoperative hyperalgesia induced by high‐dose remifentanil or sufentanil 7–9 . Nalbuphine exhibits a higher therapeutic index owing to its reduced incidence of adverse events (AEs), but has analgesic effects similar to those of morphine 10 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Moreover, because nalbuphine has very weak reactivity with delta (δ) receptors, this drug is expected to cause reduced irritability or anxiety 5,6 . In the clinical setting, pretreatment with nalbuphine can effectively reduce propofol‐induced injection pain and propofol consumption as well as ameliorate postoperative hyperalgesia induced by high‐dose remifentanil or sufentanil 7–9 . Nalbuphine exhibits a higher therapeutic index owing to its reduced incidence of adverse events (AEs), but has analgesic effects similar to those of morphine 10 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…In recent years, efforts have been made to improve the pain management of children during perioperative period [13]. Unfortunately, the number of analgesic agents available for postoperative use in pediatric populations is very limited, particularly when a patient has "nothing per oral" status [14]. In China, the operation of cleft palate repair starts around 8 months, which is earlier than the time recommended by the American Craniofacial Federation for cleft palate, Therefore, we face more di culties and challenges in postoperative analgesia [3].…”
Section: Discussionmentioning
confidence: 99%
“…It also works quickly and lasts long and therefore can be used for pediatric postoperative analgesia. 19 According to the Chinese Society of Anesthesiology, in principle, systemic opioids should be less used for patients who need surgery 20 because they often cause excessive sedation and respiratory inhibition, even nausea, vomiting, pruritus, and urinary retention. 21 A meta-analysis of randomized controlled trials showed that compared with morphine, nalbuphine had similar analgesic effects 22 but lack opioid-related adverse effects, such as itching.…”
Section: Discussionmentioning
confidence: 99%